Clause structure and word order in the history of German - Jäger, Agnes,Ferraresi, Gisella,Weiss, Helmut (Oxford University Press, 2018)
This volume presents the first comprehensive generative account of the historical syntax of German. Leading scholars in the field survey a range of topics and offer new insights into multiple central aspects of clause structure and word order, including verb placement, adverbial connectives, pronominal syntax, and information-structural factors.
10.1093/oso/9780198813545.001.0001
Keywords: Deutsch; Wortstellung; Syntax; Historische Sprachwissenschaft; Historische Syntax